1998
DOI: 10.1161/01.res.82.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Ryanodine Receptors in Smooth Muscle

Abstract: Abstract-The ryanodine receptor (RyR) in aortic and vas deferens smooth muscle was localized using immunofluorescence confocal microscopy and immunoelectron microscopy. Indirect immunofluorescent labeling of aortic smooth muscle with anti-RyR antibodies showed a patchy network-like staining pattern throughout the cell cytoplasm, excluding nuclei, in aortic smooth muscle and localized predominantly to the cell periphery in the vas deferens. This distribution is consistent with that of the sarcoplasmic reticulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 66 publications
6
62
0
1
Order By: Relevance
“…The aortic contractions caused by PI(3,5)P 2 appeared dependent on both intracellular and extracellular Ca 2ϩ . One of the mechanisms by which Ca 2ϩ is released into the cytoplasm to elicit contraction occurs through RyR channels located in the SR membrane (35). There are three molecularly distinct subtypes of RyR channels (RyR1, RyR2, and RyR3), and all three are present in the mouse aorta (24).…”
Section: Discussionmentioning
confidence: 99%
“…The aortic contractions caused by PI(3,5)P 2 appeared dependent on both intracellular and extracellular Ca 2ϩ . One of the mechanisms by which Ca 2ϩ is released into the cytoplasm to elicit contraction occurs through RyR channels located in the SR membrane (35). There are three molecularly distinct subtypes of RyR channels (RyR1, RyR2, and RyR3), and all three are present in the mouse aorta (24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MBED does not directly activate single BK channel (12). It has been suggested that Ca 2+ sparks originally occur in very narrow junctional spaces between discrete superficial SR fragments and plasmalemma (20,26,27). RyRs on the SR fragments are the target of caffeine and MBED (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution pattern of RyR follows that of the SR such that in where there is a patch distribution of SR in the cytoplasm, as in the guinea pig aorta, there is a sparse labeling with ryanodine markers, whereas tissues with a more prominent peripheral SR have a rich marking of RyR in the periphery-in other words, RyR distribution parallels that of the SR (Lesh et al, 1998). The physiological roles of RyR in smooth muscle cells are still being elucidated (Guerrero-Hernandez et al, 2002).…”
mentioning
confidence: 99%